Tracing the security dilemma in civil wars: how fear and insecurity can lead to intra-state violence - Rio Tinto, D. (2016)
The security dilemma mechanism has been widely used to explain interstate conflict since its original conceptualisation in the 1950s, but it has been applied to the study of civil wars only since the early 1990s. Despite valiant attempts, major theoretical gaps remain unaddressed in the literature, the most important of which is the missing link between the security dilemma and the outbreak of armed violence. This thesis intends to fill this gap, employing process tracing methodology on the post- independence civil wars that erupted in Angola and Mozambique after the collapse of the Portuguese empire. The research engages alternative explanations for the causes of civil war, assesses the role of the security dilemma in this context, and demonstrates that mutual insecurity was instrumental to the outcome of violence in the studied cases. Hence, this research dispels concerns about the concept's fundamental incompatibility with civil wars and advances the literature discussing several issues related to the intrastate application of an originally interstate concept. The application of the model to two novel cases enhances the theoretical and empirical relevance of the concept for the study of civil wars and reinforces claims of its potential generalisability.